Examining the Relationship Between Climate Anxiety and Mental Health Among Kabul University Students: The Mediating Role of Psychological Resilience - Mirzaee, Mohammad Jawad; Azad, Abdul Aziz; Mushtaq, Sayeed Abdulsamad (Journal of Social Sciences - Kabul University, 2025)
This study was conducted to examine the relationship between climate anxiety and mental health among students of Kabul University, with an emphasis on the mediating role of psychological resilience. The research method was descriptive–correlational, and 400 students from various faculties and fields were selected through stratified random sampling to represent the overall population of the university. The data collection instruments included the Climate Anxiety Scale by Clayton et al. (2020), the General Health Questionnaire by Goldberg and Hillier (GHQ-28), and the Connor–Davidson Resilience Scale (2003). Data were analyzed using SPSS version 26. The results showed that climate anxiety had a significant negative relationship with mental health, while psychological resilience had a positive relationship with mental health and a negative relationship with climate anxiety. Hierarchical regression analysis indicated a partial mediating role of resilience in the relationship between climate anxiety and mental health. According to the findings, increasing resilience and teaching coping skills can reduce climate anxiety and improve students’ mental health.